2008
DOI: 10.1007/s10461-008-9368-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Prevention Intervention to Reduce HIV Risk among Angolan Soldiers

Abstract: We developed and evaluated a military-focused HIV prevention intervention to enhance HIV risk-reduction knowledge, motivation, and behaviors among Angolan soldiers. Twelve bases were randomly assigned to HIV prevention or control conditions, yielding 568 participants. HIV prevention participants received training in preventing HIV (4.5 days) and malaria (0.5 days). Control participants received the reverse. Monthly booster sessions were available after each intervention. We assessed participants at baseline, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Bing et al in a study on Angolan soldiers showed increased condom use, reduced unprotected vaginal sex, and reduced numbers of partners after a training and prevention intervention (21). However, in a recent systematic review by Lopez et al long-term gains of such interventions remained understudied and clinical evidence and effectiveness of such interventions remained low and nonconclusive (22).…”
Section: Discussionmentioning
confidence: 99%
“…Bing et al in a study on Angolan soldiers showed increased condom use, reduced unprotected vaginal sex, and reduced numbers of partners after a training and prevention intervention (21). However, in a recent systematic review by Lopez et al long-term gains of such interventions remained understudied and clinical evidence and effectiveness of such interventions remained low and nonconclusive (22).…”
Section: Discussionmentioning
confidence: 99%
“…IMB model-based HIV/AIDS prevention interventions have had a significant impact in the promotion of safer sexual behavior in a wide variety of populations, including STI clinic patients (Abdala et al, 2013;Kalichman, Cherry, & Browne-Sperling, 1999;Kalichman, Williams, & Nachimson, 1999;Simbayi et al, 2004), low-income women Belcher et al, 1998;Carey et al, 2000;Carey, Maisto, et al, 1997), IDUs (Avants, Margolin, Usubiaga, & Doebrick, 2004;Calsyn et al, 2009;Copenhaver, Lee, Margolin, Bruce, & Altice, 2011;Margolin, Avants, Warburton, Hawkins, & Shi, 2003), military personnel (Bing et al, 2008;Boyer et al, 2001Boyer et al, , 2005, MSM (Bowen, Williams, Daniel, & Clayton, 2008;Mimiaga et al, 2012;Safren et al, 2011), individuals with mental illness (Carey et al, 2004;Otto-Salaj, Kelly, Stevenson, Hoffmann, & Kalichman, 2001;Weinhardt, Carey, Carey, & Verdecias, 1998), adolescent high school and older adolescent university students (Cohen, 2000;Fisher, Fisher, Bryan, & Misovich, 2002;Fisher, Fisher, Misovich, Kimble, & Malloy, 1996;Jaworski & Carey, 2001;Kiene & Barta, 2006;Lemieux, Fisher, & Pratto, 2008;Malow et al, 2009;Metzler, Biglan, Noell, Ary, & Ochs, 2000;Morrison-Beedy et al, 2013;Peeler, 2000;Rosengard, 1992;Rotheram-Borus, Gwadz, Fernandez, & Srinivasan, 1998;…”
Section: Empirical Support For Imb Model-based Hiv/aids Risk-reductiomentioning
confidence: 99%
“…Two military-setting interventions, involving men, found divergent results. A cognitive-behavioral skill-building interactive group session was found ineffective in influencing motivation or behavioral skills factors [49] while a 5 day military focused HIV prevention intervention was effective in reducing reported risky sexual behaviors and increasing HIV/AIDS knowledge [50]. Furthermore, a peer-mediated education and condom distribution program in male transport workers has been shown effective in altering AIDS related knowledge, attitude and behavior [51].…”
Section: Work-based Prevention Interventionsmentioning
confidence: 99%